Chilling and forcing requirement of five international fig cultivars grown in Southeastern Brazil - Honorato Monteiro, Laís Naiara; Leonel, Sarita; Mirellys Azevedo Souza, Jackson; Bibiano Ferreira, Rafael; de Souza Silva, Marcelo; Loli Garcia, Emerson (Revista Ceres, 2022)
Chill hours availability influence break dormancy, sprouting and production of temperate fruits trees in different regions. However, there are few reports on the subject for fig tree. This study aimed to evaluate the effects of the accumulated chilling hours on the physiology and dormancy release of fig cultivars. Stem cuttings of five fig cultivars were collected at the end of winter over two crop cycles and exposed to 0, 40, 80, 120 and 160 accumulated chilling hours (CH) in a cold chamber (8±0.5 oC). Physiology of fig buds was then evaluated with regards to antioxidant enzymes activity, carbohydrate and nitrogen contents. The exposure of fig stem cuttings with two buds to different accumulated CH presented physiological changes for antioxidant enzymes activity, carbohydrates and nitrogen contents and confirming that the cultivars responded differently to the climatic conditions of each crop cycle. Results detected that the lowest accumulated CH in field in 2018 (2.7 CH) enabled a greater effect of the artificial CH when compared to 2017 (19.5 CH). Each fig cultivar had a critical accumulation point. The cultivars Roxo de Valinhos and Pingo de Mel require less CH to break dormancy, while Troyano requires more CH to finish this vegetative rest period.